STUDY OF PSYCHOLOGICAL, EMOTIONAL AND MINDFULNESS STATUS IN AGE-MATCHED ANAPANASATI MEDITATORS AND NON-MEDITATORS AS TRACKED USING NONINVASIVE TOOLS-ELECTROPHOTONIC IMAGING - Guru Deo; Srinivasan, Thaiyar M; S. K. Rajesh (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The aim of the current study is to explore the status of energy pattern, stress and psychological well-being in age-matched meditators (M) and non-meditators (NM) as assessed by Electrophotonic Imaging and psychological measures.There were 93 subjects consisting of 45 meditators (practicing meditation from last 6 months and longer (mean months of practice 61.18  50.08, daily 1.63 2.14hours) and 48 non-meditators. There were total 88 participants where 43 meditators (male and female, mean age 32.64 7.09years) and 45 non-meditators (mean age 30.31 6.45years) in the study.  Assessment done using Electrophotonic Imaging (EPI), Self-control Scale (SCS), Emotion Regulation Questionnaire (ERQ), Freiburg Mindfulness Inventory (FMI) and General Health Questionnaire (GHQ).Meditators revealed lower stress, disorderliness at energy level in comparison to non-meditators on EPI parameters. Self-control score, scores of mindfulness and general health was significant and highly significant respectively in meditators as compared to non-meditators. Emotional regulation score was positive where reappraisal and suppression scores were found contributory in current research but not significant.Psychophysiological status of meditators showed less stress, less suppression and positive emotion regulation in comparison to non-meditators. In conclusion, meditators exhibited better self-control, better energy availability, mindfulness and good health.